Business Strategy for Minimizing Taxes: (Empirical Study of Consumer Goods Industry Sector Companies Listed on the Indonesian Stock Exchange for the 2018-2022 Period) - Herawati, Hetti; Naufal, Yogascitra; Lusiana, Senny; Audina4, Novi Rizka (International Journal of Management and Business Applied, 2024)
This research aims to find out whether the prospector and defender business strategy with 4 proxies, consisting of production & distribution capabilities, company growth level, marketing and fixed asset intensity, is able to minimize taxes owed. From the 71 population of consumer goods industry companies listed on the Indonesia Stock Exchange (BEI) in the 2018-2022 period, a sample of 15 companies was obtained. with 75 observations. This research uses a descriptive method with a quantitative approach. The analytical method used is panel data regression analysis. The research results show that partially each proxy has no effect in minimizing taxes. Meanwhile, simultaneously a business strategy consisting of 4 proxies has an influence in minimizing the tax owed. The research results show that both the defender and prospector strategies implemented by the Company both have the potential to minimize taxes owed.